Do perioperative antibiotics reduce the risk of surgical‐site infections following excision of ulcerated skin cancers? A Critically Appraised Topic. (1st February 2018) - Chan, S.A.; Wernham, A.G.H.; Stembridge, N.; Harper, N.; Verykiou, S.; Fremlin, G.A.; Abbott, R.A.; Matin, R.N.
Summary: Skin cancer is the commonest type of cancer in the United Kingdom and the numbers are increasing worldwide. Most skin cancers are treated with surgery to remove the cancer from the skin. The risk of having a wound infection after skin surgery is less than 5%. Current evidence suggests that this risk is increased if there is a break on the surface of the skin cancer – called ulceration. At present, there is no guidance in the U.K. for using antibiotics after skin surgery to potentially reduce the risk of infection. This report aimed to review all the research evidence available to help doctors decide if prescribing antibiotics to patients having skin cancers removed by surgery, reduces the chances of wound infection after their skin surgery. A total of 1018 scientific articles were identified in the English Language. The team identified 13 trials as high quality (called randomised controlled trials) where different types of antibiotics were used to see if they reduced infection rates after skin surgery. These included antibiotics applied on the wound surface, antibiotics ingested by mouth, antibiotics given by injection into the muscle or directly into the bloodstream. The research team concluded that based on this review there is not enough evidence to show that taking any form of antibiotic reduces the chances of wound infections following skin cancer surgery. The authors recommend that in the future, researchers should perform a well‐designed clinical trial to answer this question, as this may help prevent some people receiving antibiotics after skin surgery when it may not be needed.